Del horror a la costumbre: Violencia y política en el México actual - Constantino Toto, Mario C. (1997)
At dawn on January 1, 1994, the discordant note of the celebrations of Mexico's entry into the club of rich countries was placed in the highlands of Chiapas, in the south of the country, by an armed group that formally declared war to the government of the Republic. Undoubtedly, more than one of the New Year's Eve guests felt how the few certainties built around the dream of national modernization were suspended on the thin thread of uncertainty.